2017
DOI: 10.1007/s11881-017-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexie font does not benefit reading in children with or without dyslexia

Abstract: In two experiments, the claim was tested that the font “Dyslexie”, specifically designed for people with dyslexia, eases reading performance of children with (and without) dyslexia. Three questions were investigated. (1) Does the Dyslexie font lead to faster and/or more accurate reading? (2) Do children have a preference for the Dyslexie font? And, (3) is font preference related to reading performance? In Experiment 1, children with dyslexia (n = 170) did not read text written in Dyslexie font faster or more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
(62 reference statements)
4
28
2
2
Order By: Relevance
“…This was an expected result since in this unusual spacing condition, it is difficult to segment sentences into words because the sizes of the (increased) inter-letter and the (default) inter-word spacing appeared similar. However, contrary to several studies (Bachmann, 2013;Marinus et al, 2016;Zorzi et al, 2012), but in line with other previous research (Damiano, Gena, & Venturini, 2019;Kuster et al, 2017), a general advantage in reading speed due to increased spacing, in both its components, was not found either in children with dyslexia or in typical readers. The difference between default and increased spacing employed in the present study was smaller than that used in the study by Zorzi et al (2012), where the authors, using exceptionally wider spacing, found a positive effect on fluency in Italian and French readers.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This was an expected result since in this unusual spacing condition, it is difficult to segment sentences into words because the sizes of the (increased) inter-letter and the (default) inter-word spacing appeared similar. However, contrary to several studies (Bachmann, 2013;Marinus et al, 2016;Zorzi et al, 2012), but in line with other previous research (Damiano, Gena, & Venturini, 2019;Kuster et al, 2017), a general advantage in reading speed due to increased spacing, in both its components, was not found either in children with dyslexia or in typical readers. The difference between default and increased spacing employed in the present study was smaller than that used in the study by Zorzi et al (2012), where the authors, using exceptionally wider spacing, found a positive effect on fluency in Italian and French readers.…”
Section: Discussionsupporting
confidence: 75%
“…Both children with dyslexia and typical readers did not show differences in reading performance in terms of reading speed and accuracy when they read texts written with the DF letterform or with the standard letterform. These results could be interpreted as additional evidence (see Kuster et al, 2017;Wery & Diliberto, 2017) that the particular letterform of the dyslexiafriendly fonts, which includes dedicated serifs, longer ascenders/descenders, and asymmetry of characters similar in shape, did not produce any advantage in reading over the letterform of common fonts.…”
Section: Discussionmentioning
confidence: 72%
“…Even though the remaining item 5, “enlarging the size of font or marking where you read can improve reading,” had a poor factor loading, we did not removed it because the index did not become better after removing it. Additionally, there was evidence suggesting the larger font size can help children with dyslexia to improve reading speed ( Kuster et al, 2017 ). Thus, we believed that the DCCC would make more sense by including it.…”
Section: Discussionmentioning
confidence: 99%
“…The readability of a text depends on a large number of the features of the font in which the text is written. The features are always interrelated and generally, they include: character size, space between the characters and rows and shape of the font (Kuster, van Weerdenburg, Gompel and Bosman, 2018). Research shows that the fonts with bigger size are much more easily readable (Perea, Panadero, Moret-Tatay & Gómez, 2012).…”
Section: Features Of Dyslexia Fontsmentioning
confidence: 99%